Clinical Study of Severe Cutaneous Adverse Reactions to Drugs ... - Debajit Das; Shahjubin Basir (International Journal of Pharmaceutical and Clinical Research, 2023)
Background: Adverse drug reaction is defined as ‘an undesirable clinical manifestation resulting from administration of a particular drug; this includes reaction due to overdose, predictable side effects and unanticipated adverse manifestations’. 1 of every 1000 hospitalized patients has a serious cutaneous drug reaction. SJS and TEN are associated with severe morbidity and mortality. The fatality rate in SJS is reported to be 5-10%, while in TEN it is reported to be 25-30%. So, the following study shall thus be a sincere effort to explore more about the adverse drug reactions. Objectives: To study the different clinical patterns of SCAR, and to identify the offending drugs causing different types of SCAR. Methods: The study has been conducted in the department of Dermatology, Silchar Medical College & Hospital, and Silchar, Assam over a period of one year extending from 1st June 2018 to 31st May 2019 after approval from the Institutional Ethics Committee (IEC) and after obtaining informed consent from ... : Background: Adverse drug reaction is defined as ‘an undesirable clinical manifestation resulting from administration of a particular drug; this includes reaction due to overdose, predictable side effects and unanticipated adverse manifestations’. 1 of every 1000 hospitalized patients has a serious cutaneous drug reaction. SJS and TEN are associated with severe morbidity and mortality. The fatality rate in SJS is reported to be 5-10%, while in TEN it is reported to be 25-30%. So, the following study shall thus be a sincere effort to explore more about the adverse drug reactions. Objectives: To study the different clinical patterns of SCAR, and to identify the offending drugs causing different types of SCAR. Methods: The study has been conducted in the department of Dermatology, Silchar Medical College & Hospital, and Silchar, Assam over a period of one year extending from 1st June 2018 to 31st May 2019 after approval from the Institutional Ethics Committee (IEC) and after obtaining informed consent from ...